SOTSIOLINGVISTIKADA O‘RGANILADIGAN MASALALAR XUSUSIDA («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article provides information about the origin, goals and tasks of the science of sociolinguistics, the subject and object of research. Also, issues such as variability, linguistic community and its means of communication, sociolinguistic classification of languages, linguistic situation and language policy are covered in detail.
Keywords: Sociolinguistics, variation, linguistic community, slang, slang, linguistic situation, language policy, pidgin and creole languages.